Escravos em ação na Comarca do Príncipe - Província do Rio Grande do Norte (1870-1888) - Pereira, Ariane de Medeiros (2014)
The aim of this research is to study the actions of slaves in Comarca do Príncipe, Rio Grande do Norte (1870/1888). Considering the space as a relevant category in the subservient relationship, we investigate how negotiations about the captivity conditions and freedom took place in the domain of this province. The slaves are considered as subjects, who fought for better living conditions in the captivity and who sometimes practiced criminal offenses to achieve freedom. To analyze their actions in the socio-economic environment of the province, we resort to different types of sources. They are: civil and criminal processes, reports from the president of Rio Grande do Norte, the census of 1872, a newspaper called O Assuente, the Livro do Fundo de Emancipação do Município de Príncipe (1873-1886) (The Emancipation Book of Príncipe city) and Imperial Laws. We used the following steps to analyze the data obtained from these sources: the compilation, reading, paleographic transcription, classification of the data according to the thematic, analysis and comparison of information and statistic quantification, submitting empirical data to the discussion built according to the historiographies debates about this subject